Congenital diaphragmatic hernia in a case of Cat eye syndrome. Issue 9 (23rd July 2018) - Alsat, Ebru Aileen; Reutter, Heiko; Bagci, Soyhan; Kipfmueller, Florian; Engels, Hartmut; Raff, Ruth; Mangold, Elisabeth; Gembruch, Ulrich; Geipel, Annegret; Müller, Andreas; Schaible, Thomas
Key Clinical Message: Our findings extend the phenotypic spectrum of Cat eye syndrome, a disorder with wide clinical variability. The potentially life‐threatening complications of congenital diaphragmatic hernia should be considered in genetic counseling and prenatal diagnostic. Abstract : Our findings extend the phenotypic spectrum of Cat eye syndrome, a disorder with wide clinical variability. The potentially life‐threatening complications of congenital diaphragmatic hernia should be considered in genetic counseling and prenatal diagnostic.